1977
DOI: 10.1210/jcem-45-3-601
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Insulin Action: A Probable Mechanism for the Anti-Diabetic Action of Sulfonylurea Drugs

Abstract: Insulin action was assessed by measuring insulin-mediated glucose disposal (KI) in 13 non-ketotic diabetic patients both before treatment and after normalization of plasma glucose by diet (5 patients) or sulfonylurea (glipizide) therapy (8 patients). While the KI of the diet-treated group was unchanged by therapy, that of the glipizide-treated group was significantly increased. The data show that chronic glipizide therapy is associated with a potentiation of insulin action, which may account for the major anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…In another aspects, there is a report that gliclazide could enhance insulin signaling in insulin-resistant mouse skeletal muscle cells, but insulin-stimulated actual glucose uptake was unaffected (Kumar and Dey, 2002). Moreover, experiments performed in normal dogs showed that glimepiride had the highest total blood glucose-lowering activity during the 36-h post-treatment period when compared with glibenclamide, gliclazide, and glipizide (Lebovitz et al, 1977). Consistent with the present finding, there has been no observation reported for repaglinide to have extrapancreatic activity.…”
Section: Discussionsupporting
confidence: 88%
“…In another aspects, there is a report that gliclazide could enhance insulin signaling in insulin-resistant mouse skeletal muscle cells, but insulin-stimulated actual glucose uptake was unaffected (Kumar and Dey, 2002). Moreover, experiments performed in normal dogs showed that glimepiride had the highest total blood glucose-lowering activity during the 36-h post-treatment period when compared with glibenclamide, gliclazide, and glipizide (Lebovitz et al, 1977). Consistent with the present finding, there has been no observation reported for repaglinide to have extrapancreatic activity.…”
Section: Discussionsupporting
confidence: 88%
“…The increased diabetic patients have demonstrated that plasma insulin levels insulin sensitivity in vitro may be caused by a higher number, often return to pretreatment levels even though the binding affinity or tyrosine kinase activity of the insulin receptor. sulphonylurea-induced hypoglycaemic effect persists (Simonson However, the evidence available strongly points toward a postet al., 1970Lebovitz et al, 1977;Greenfield et al, 1982; receptor effect (Maloff and Lockwood, 1981;Davidson and Kolterman et al, 1984;Mandarino and Gerich, 1984;Ward Sladen, 1987;Jacobs et al, 1987;Bak et al, 1989), which would et al 1985). Thus these compounds possess the interesting also explain the stimulation of glucose transport in the absence additional property of increasing glucose uptake and utilization of insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Sulphonylurea, there¬ fore, seems to intensify the effect of insulin. An evidence for this hypothesis has recently been given by Lebovitz et al (1977) by studying the insulin sen¬ sitivity in non-ketotic diabetics treated with giipizide.…”
mentioning
confidence: 97%